2018
DOI: 10.1002/bbb.1901
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of recovery of volatile fatty acids and mixed ketones as alternative downstream processes for acetogenisis fermentation

Abstract: Carboxylates produced by the acetogenisis fermentation of pre‐treated lignocelluloses are precursors to bio‐based products that are alternatives to second‐generation biofuels for biomass valorization. This paper compares the techno‐economic indicators for recovering either mixed ketones or mixed volatile fatty acid (VFA) products from the carboxylates in a fermentation broth through process simulation and financial modeling. This study considers scenarios for (i) an efficient process for ketone production (K‐P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The utility cost of separation and purification accounts 60% [27] to 80% [6] of whole production cost of acids. Considering mixed acid price of $2.70/kg [54] and solvent loss equivalent to 3% of product amount, the utility cost is low enough to apply the proposed scheme to up-scaling processes.…”
Section: Resultsmentioning
confidence: 99%
“…The utility cost of separation and purification accounts 60% [27] to 80% [6] of whole production cost of acids. Considering mixed acid price of $2.70/kg [54] and solvent loss equivalent to 3% of product amount, the utility cost is low enough to apply the proposed scheme to up-scaling processes.…”
Section: Resultsmentioning
confidence: 99%
“…An economic sensitivity analysis is used to identify the important parameters on viability and profitability of the various scenarios. (Assessment, Selected and Gorgens, 2016;Petersen, Franco and Görgens, 2018) b (Gerbrandt, 2014;Biddy et al, 2016) c (Llzo and Lx, no date) d Considered improved or similar feed value as BSG (Tucker et al, 2004) e Based on protein content using $1/kg protein f Price of molasses g Based on protein content wet basis h (Michael O'Donohue, 2014;Clauser et al, 2015) Results…”
Section: Capital Expenditure (Capex) Estimationmentioning
confidence: 99%
“…All authors provided input to the manuscript and read and approved the final manuscript. Hong et al, 2014;Clauser et al, 2015;Petersen, Franco and Görgens, 2018) c Averages from reported literature Hong et al, 2014;Clauser et al, 2015;Petersen, Franco and Görgens, 2018) d e (Wooley, 1997;Wan, Xie and Nancy Ho, 2003) f (Wan, Xie and Nancy Ho, 2003) 6.2.3.2 Discounted cash flow Calculation of total cost of production (TCP) for a product such as xylitol will give an estimate of breakeven cost for xylitol. If market prices for xylitol are lower than TCP and there are no other revenues from production the biorefinery concept will be unprofitable.…”
Section: Authors' Contributionsmentioning
confidence: 99%
“…The xed capital investment (FCI) was assumed 1500 USD/Kg FW and it was based in Colombian prices estimates. The economic assumptions used included: 1) the plant life was 20 years, 2) the annual labour and operational costs were assumed to be 25% and 21% of the FCI (Petersen et al 2018). 3) the FCI for scaling up the VFA biore nery plant was de ned by Equation 1.…”
Section: Economic Assessmentmentioning
confidence: 99%